Luteal changes after treatment with sub-luteolytic doses of prostaglandin (cloprostenol sodium) in cattle - Trevisol, Eduardo [UNESP]; Ferreira, Jair Camargo [UNESP]; Ackermann, Camila Louise [UNESP]; Destro, Flavia Caroline [UNESP]; Marques Filho, Wolff Camargo [UNESP]; Carmagos, Aline Souza [UNESP]; Biehl, Marcos Vinicius; Amaral, Jackson Barros do; Pantoja, José Carlos de Figueiredo [UNESP]; Sartori, Roberto; Pinheiro Ferreira, João Carlos [UNESP] (Elsevier B.V., 2015)
This study characterizes the physiological and morphological changes related to partial luteolysis in bovine corpus luteum (CL) after challenges with sub-doses of cloprostenol sodium on Day 6 (D6) of the estrous cycle. Cows (n =12/treatment) were treated as follows: Control (2 mL, saline, i.m.); 2XPGF (two treatments i.m. 500 mu g of cloprostenol sodium 2 h apart) and 1/6PGF (83.3 mu g of cloprostenol sodium, i.m., once). Plasma progesterone (P4) concentration, CL volume and blood flow were measured immediately before the treatments, then every 8 h (h) for 48 h. In the Control, P4 concentrations were higher at 48 h than at Oh. P4 decreased 8 h after 2XPGF treatment (P< 0.05), and remained low until the end of the trial. P4 decreased in 1/6PGF between 8 and 16 h (P< 0.05), then began to rebound at 24 h. Luteal volume was higher in Controls at 48 h than at Oh. Under 1/6PGF, luteal volume decreased at 24 h (P <0.05) and began to rebound at 32 h. Luteal volume and blood flow were reduced starting at 24 and 32 h, respectively, after 2XPGF treatment (P< 0.05). In this study, we were able to describe the partial luteolysis phenomenon, induced by a treatment of a D6CL with cloprostenol sub-dose.
Keywords: Cow; Corpus luteum; Partial luteolysis